The mediating role of emotion in the effects of landscape elements on thermal comfort: A laboratory study. (1st April 2023) - Yan, Tingkai; Jin, Hong; Jin, Yumeng
Abstract: Comfortable, enjoyable outdoor spaces are critical to human health and well-being. The emotional reactions induced by various combinations of visual landscapes and the role of emotion in outdoor thermal comfort are unknown. As such, by simulating outdoor temperatures during the winter and summer seasons in the lab, this study investigates the effects of various landscape elements on emotion and thermal comfort and the role of emotion in this from a psychological perspective. The results show that emotions play a mediating role in the effects of landscape elements on thermal comfort. Notably, seasonal differences significantly impact the mediating role of emotions. In summer, the direct effect of landscape elements on thermal comfort was insignificant; however, the direct effect was significant in winter. Additionally, the three dimensions of emotion showed significant differences in various streetscapes. Pleasure had the highest effect on thermal comfort, while arousal had the weakest effect. Different combinations of landscapes can affect emotional scores and thermal comfort evaluations. The effects of the landscape on emotions and thermal comfort differ significantly between summer and winter. This research aims to guide landscape architects in creating a streetscape environment with better thermal comfort and emotional experience, eventually contributing to creating a healthy and liveable city. Highlights: Emotions play a mediating role in the effects of landscape elements on thermal comfort. Landscape affects thermal comfort differently across the three dimensions of emotion. Emotional pleasure had the highest effect on thermal comfort and acceptability. Seasonal differences have a significant impact on the mediating role of emotions. The landscape is more difficult to activate for the dimension of arousal in the winter.